KEKUATAN KEARIFAN LOKAL DALAM KOMUNIKASI KESEHATAN - Rini Darmastuti, Dewi Kartika Sari (IKOM UMY, 2015)
So far, traditional medicines and traditional treatments are often underestimated and considered outdated or sometimes even considered to exacerbate an illness. When in fact, medicines and the traditional ways in healing the disease, they helped the healing. The locol knowledge possessed by the people of Indonesia, has many positive sides, including in health. We can use traditional medicines and traditionol ways to treat disease. lJnfortunotely, knowledge of local wisdom is not widely taught in schools and in health higher education. Knowledge of local wisdom, culture, and the approoch to local society is less focus of the study, whereos these three things actuolly become urgency for students in health education. Therefore, in this paper we will discuss about the medical necessity to know the local wisdom of the local